Absenteísmo de pacientes na primeira consulta na oncologia cirúrgica do centro de referência da saúde da mulher – hospital Pérola Byington - Fernandes, Rosana Ávila (2019)
With the creation of the Regulation Center for Health Services Offers (CROSS), it is possible to verify that there is still impoundment in outpatient care, since there is absenteeism of the patients in their consultations and examinations. The objective of this research was to demonstrate and identify the causes and rates of absenteeism in the specialty of Surgical Oncology of the Center for Reference of Women's Health (CRSM) - Pérola Byington Hospital in the first consultation scheduled through CROSS and the outcome they had abstained of the consultations, if they were able to reschedule, if they remained untreated or if they died, by analyzing the time of each appointment, the municipality of residence, age group and requesting appointment, and also by absent patients who agreed to participate in the study. An evaluation by the Director of Surgical Oncology of the CRSM of the patients who remained untreated during the study period was carried out so that they could be rescued so that there would be no greater harm to their treatments. A retrospective and longitudinal case study was carried out for the period from April 2014 to June 2018, with a qualitative approach, verifying which patients were absent and who remained untreated; prospective study, using primary data through questionnaires during the period from August 5 to November 29, 2018 with patients absent at first consultation at the CRSM and medical evaluation using descriptive statistics for analysis and interpretation of the data. Data were analyzed through CROSS management reports. The age range of patients who were absent in the consultation was 60 years or more, the time between the date of appointment and the date of consultation was up to 10 in 75.84% of the cases. The rate of 73.17% of inability to contact the absent patients was noted in this study. Absenteeism generates losses for the patient, for the service and increase in the queue of waiting.